# Solve each of the following quadratic equations:x2 - (2b - 1)x + (b2 - b - 20) = 0

x2 - (2b - 1)x + (b2 - b - 20) = 0

Using the splitting middle term - the middle term of the general equation is divided in two such values that:

Product = a.c

For the given equation a = 1; b = - (2b - 1); c = b2 - b - 20

= 1(b2 - b - 20)

= (b2 - b - 20)

And either of their sum or difference = b

= - (2b - 1)

Thus the two terms are - (b - 5) and - (b + 4)

Sum = - (b - 5) - (b + 4)

= - b + 5 - b - 4

= - 2b + 1

= - (2b - 1)

Product = - (b - 5) - (b + 4)

= (b - 5) (b + 4)

= b2 - b - 20

x2 - (2b - 1)x + (b2 - b - 20) = 0

x2 - (b - 5)x - (b + 4)x + (b - 5)(b + 4) = 0

x[x - (b - 5)] - (b + 4)[x - (b - 5)] = 0

[x - (b - 5)] [x - (b + 4)] = 0

[x - (b - 5)] = 0 or [x - (b + 4)] = 0

x = (b - 5) or x = (b + 4)

Hence the roots of equation are (b - 5) or (b + 4)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Get To Know About Quadratic Formula42 mins  Quiz | Knowing the Nature of Roots44 mins  Take a Dip Into Quadratic graphs32 mins  Foundation | Practice Important Questions for Foundation54 mins  Nature of Roots of Quadratic EquationsFREE Class  Getting Familiar with Nature of Roots of Quadratic Equations51 mins  Quadratic Equation: Previous Year NTSE Questions32 mins  Champ Quiz | Quadratic Equation33 mins  Balance the Chemical Equations49 mins  Champ Quiz | Quadratic Equation48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 